Newborn Screening in a Pandemic—Lessons Learned - Matej Mlinaric; James R. Bonham; Viktor Kožich; Stefan Kölker; Ondrej Majek; Tadej Battelino; Ana Drole Torkar; Vanesa Koracin; Dasa Perko; Ziga Iztok Remec; Barbka Repic Lampret; Maurizio Scarpa; et al. (International Journal of Neonatal Screening, 2023)
The COVID-19 pandemic affected many essential aspects of public health, including newborn screening programs (NBS). Centers reported missing cases of inherited metabolic disease as a consequence of decreased diagnostic process quality during the pandemic. A number of problems emerged at the start of the pandemic, but from the beginning, solutions began to be proposed and implemented. Contingency plans were arranged, and these are reviewed and described in this article. Staff shortage emerged as an important issue, and as a result, new work schedules had to be implemented. The importance of personal protective equipment and social distancing also helped avoid disruption. Staff became stressed, and this needed to be addressed. The timeframe for collecting bloodspot samples was adapted in some cases, requiring reference ranges to be modified. A shortage of essential supplies and protective equipment was evident, and laboratories described sharing resources in some situations. The courier system had to be adapted to make timely and safe transport possible. Telemedicine became an essential tool to enable communication with patients, parents, and medical staff. Despite these difficulties, with adaptations and modifications, some centers evaluated candidate conditions, continued developments, or began new NBS. The pandemic can be regarded as a stress test of the NBS under real-world conditions, highlighting critical aspects of this multidisciplinary system and the need for establishing local, national, and global strategies to improve its robustness and reliability in times of shortage and overloaded national healthcare systems.